Chapare mammarenavirus - a new deadly virus outbreak: a review - Gujar, Dnyaneshwari; Choudary, N. Sriram; Joshi, Chaitrali; Raigir, Nikhitha; Sharma, Shreshth; Babu, Kommuri Baji; Tiwari, Rahul V. C. (International Journal of Research in Medical Sciences, 2020)
In 2003 an emerging mammarenavirus (formerly arenaviruses) was discovered in Bolivia and named Chapare (CHAPV). It was related to severe and fatal haemorrhagic fever, being similar in clinical features to Machupo (MACV). In mid-2019, CHAPV was the explanation for a cluster of 5 cases, two of them laboratory confirmed, three of them fatal. Reverse transcription polymerase chain reaction (RT-PCR) analysis and subsequent analysis of the entire virus S and L ribonucleic acid (RNA) segment sequences identified the virus as a member of the New World Clade B arenaviruses, which includes all the pathogenic South American arenaviruses. The virus was shown to be most closely associated with Sabia´ virus, but with 26% and 30% nucleotide difference within the S and L segments, and 26%, 28%, 15% and 22% aminoalkanoic acid differences for the L, Z, N, and GP proteins. LUJV, CHAPV, GTOV, and SABV, which are geographically restricted, have been associated with only a few to a few dozen cases. They are, therefore, relatively unimportant to clinicians compared to many other viruses that are usually co-endemic. However, MACV, JUNV, and especially LASV have caused large outbreaks (LASV has caused hundreds of thousands of infections per year). Visitors to countries in which these viruses are endemic, or war-fighters that are deployed to these countries, need to be aware of how to prevent and suspect a mammarenavirus infection.